Parenteral Nutrition Use and Associated Outcomes in a Select Cohort of Low Birth Weight Neonates - Robinson, Daniel T.; Shah, Shreya; Murthy, Karna (American Journal of Perinatology, 2014)
Objective The aim of this study is to assess the influence of parenteral nutrition (PN) on the time to regain birth weight in premature neonates born between 1,500 and 2,499 g.Study Design A retrospective analysis stratified premature neonates born between 1,500 and 2,499 g by receipt of PN or intravenous dextrose at ≤ 72 hours of age. The primary outcome was the time to regain birth weight. Secondary measures included preterm-associated morbidities, time to achieve predefined enteral nutrition milestones, and length of stay. Multivariable regression estimated associations between PN and time to achieve nutrition milestones.Results Among 260 eligible neonates, those receiving PN (53%) were less mature, weighed less at birth, had a higher index of illness severity, and higher prevalence of preterm-associated morbidities (p < 0.01). The time to regain birth weight (PN, 9.4 ± 3.5 d; no PN, 9.5 ± 3.4 d) was similar between groups. Regression analysis adjusting for gestational age, illness severity, and sepsis demonstrated that PN exposure was associated with a greater time to achieve nutrition milestones and length of stay (p < 0.05).Conclusion Although its impact on growth remains uncertain among premature neonates born between 1,500 and 2,499 g, PN was independently associated with a greater time to achieve nutrition milestones.
Keywords: parenteral nutrition; neonate; growth; low birth weight; premature